Evaluating deterministic asynchronous disk benchmarking using the linux asynchronous I/O - Rahmalia Syahputri; Rizky Juniardi (Institut Teknologi Sepuluh Nopember, 2026)
Accurate storage performance characterization in virtualized environments requires benchmarking tools with minimal runtime overhead. Conventional asynchronous I/O introduces scheduling overhead and latency variability, degrading measurement stability. This study designs and evaluates Calyx, a deterministic disk benchmarking tool built on Linux io_uring that integrates submission queue polling, fixed resource registration, and an allocation-free I/O path. Evaluation on HyperV virtualized NVMe compared Calyx against fio. Under sequential reads on ext4, Calyx achieves 4,576.92 MB/s throughput with 0.18% CV and 3,979.54 μs P99 latency, versus fio's 4,560.49 MB/s, 0.73% CV, and 5,210.11 μs P99 latency. For sequential writes on XFS, Calyx maintains 3,320.09 MB/s (2.25% CV, 9,529.98 μs P99) while fio drops to 1,388.92 MB/s (49.57% CV, 39,059.46 μs P99), which is plausibly attributed to SSD cache exhaustion. CPU utilization for Calyx scales flatly from 49.5% (QD=8) to 53.1% (QD=64), whereas fio scales linearly from 35.2% to 59.8%. Calyx's deterministic pipeline reduces measurement variability without sacrificing throughput, confirming that registered-resource execution improves benchmarking reliability in virtualized systems.